The Greek polis and the invention of democracy: a politico-cultural transformation and its interpretations - Jóhann Páll Árnason; Raaflaub, Kurt A.; Wagner, Peter (Wiley-Blackwell, 2013)
"The Greek Polis and the Invention of Democracy presents a series of essays that trace the Greeks' path to democracy and examine the connection between the Greek polis as a citizen state and democracy as well as the interaction between democracy and various forms of cultural expression from a comparative historical perspective and with special attention to the place of Greek democracy in political thought and debates about democracy throughout the centuries."--Publisher's website
Includes bibliographical references and index
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Greece -- Politics and government -- To 146 B.C; Greece -- Social conditions -- To 146 B.C; Konferenzschrift -- 2006 -- Fiesole; Aufsatzsammlung; Demokratie; Polis; Geschichte; Demokratisierung; Griechenland